PENGARUH LOKASI DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN RUMAH DI PD RAHARJA CIMAHI - Sulastri, Ai; Prasetiyo, Budi (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2022)
This research is a quantitative study on PD Raharja Cimahi that seeks to analyze how location and promotion influence judgments regarding the purchase of a home, as well as the extent to which these factors have an impact. The sample for this investigation consisted of 68 participants who were selected through the process of probability sampling using the technique of multiple linear regression analysis. Based on the study findings that the value of R2 is 0.535, which is equivalent to 53.5%, suggests that the findings of this study reveal the influence of location on consumer purchasing decisions. A simultaneous influence on customer purchasing decisions of 0.463%, or 46.3%, is exerted through promotion. The results of the tests on the hypotheses suggest that the elements of location and promotion have a positive impact on the decisions on which products to purchase. The value of R^2, which is 0.535%, reflects this point of view accurately. With a value of R = 20.535, it is possible to deduce that the independent elements in this investigation, namely location and promotion, have an influence on consumer spending decisions that is equivalent to 53.5%. The factors of location and promotion have a large influence on purchase decisions, with an effect size of 53.5%. Meanwhile, the remaining influence comes from factors that were not investigated in this study.